ANALYSIS OF CUSTOMER SATISFACTION SPORT AND RECREATIONAL AMENITIES HOTELS IN NOVI SAD - Miodrag Koprivica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
In order to ensure the satisfaction of the users, the hotels are expanding their offer with various sports and recreational facilities. The basic requirements for the realisation of the sports and recreational programmes are expert staff, adequate space and interesting programme. The aim of this paper is to determine the satisfaction of the users with certain aspects of the quality of the sports and recreational offer in four Novi Sad hotels. There were 98 respondents involved in the research. The results showed that there are significant differences in the evaluation of the quality in terms of prices, working hours, programme content and the hotel accessibility. The results also showed that the hotel rank is not related to the users' satisfaction with the quality of the sports and recreational facility offer. Constant innovations of the locales and their equipment, the personalisation of the sports and recreational programmes, hiring expert staff and sports animators but also adjusting all of the offer elements to the local population is essential to achieve users' satisfaction with the sports and recreational offer and generate the income for the organisation - hotel.